ANALYSIS OF ISLAMIC EDUCATION SUPERVISION APPROACH BASED ON ISLAMIC VALUES - Edi Supriyatno; Sarnubi; Syamsuarni; Almahfuz; Istiqamah (Journal International Inspire Education Technology, 2026)
Supervision of Islamic education is an important component in improving the quality of education because it not only functions as a technical supervision mechanism, but also as a process of professional, moral, and spiritual development of teachers within the framework of Islamic values. This study aims to analyze various approaches to Islamic education supervision and formulate the most relevant approaches based on the integration of Islamic values. The research uses a literature study approach with data collection techniques through documentation of various relevant scientific literature sources, then analyzed using content analysis to find patterns, main themes, and conceptual tendencies of various supervision approaches. The results of the study show that Islamic education supervision includes directive, non-directive, collaborative, clinical, and Islamic values-based approaches, each of which has different characteristics and uses according to the context of teachers and institutions. However, a collaborative approach based on Islamic values has proven to be the most relevant because it is able to integrate professionalism, active participation, and spirituality in an integrated manner. The values of trust, ihsan, deliberation, rahmah, and tawadhu strengthen the effectiveness of supervision and form a religious and productive academic culture. Thus, effective Islamic education supervision needs to be designed in a contextual, collaborative, and rooted in Islamic values in order to be able to improve the quality of education in a sustainable manner